Rancang Bangun Sistem Charging dan Monitoring Baterai pada PLTPh Berbasis IoT - Kumala Mahda Habsari; Hanifah Nur Kumala Ningrum; R. Jasa Kusumo Haryo; Faisal Rachman Kuncoro (FORTEI Regional VII Jawa Timur, 2022)
A pico-hydro power plant (PLTPh) is a small-scale power generation system that utilizes the height difference and the amount of water discharge per second that exists in the water flow of irrigation canals, rivers and waterfalls. Uncertain natural and weather conditions at the PLTPh location, causing the water flow to become unstable and can overflow. Instability in the flow of water can also affect the performance of the generator, from the turbine and generator side. The voltage generated by the generator becomes unstable and can result in the effect of charging the battery which can damage the battery. In this study, a design and construction of a battery charging and monitoring system for PLTPh based on the Internet of Things (IoT) was created. This research aims to make battery charging and monitoring in real time using IoT technology integrated with the thinger.io website. The result of this study is a charging device (charger) with the non-inverting buck boost converter method. The charger can work properly by producing an output voltage according to the desired voltage set point for charging the battery, which is 14.6 volts. The sensors work fine. RPM (rotation) sensors, voltage sensors and current sensors work well with an error value difference of less than 5% during testing. The water flow sensor for measuring water discharge works well, the ultrasonic sensor works well with a 0% error value test. When the ultrasonic sensor detects the distance is less than the specified set point (10 cm), the buzzer sounds to alarm when the water overflows so that the generator does not sink. The charger relay and generator protection relay are working properly. The data read by the sensor can be displayed on the LCD and the thinger.io website.